Extracts of Dracocephalum tanguticum Maxim Ameliorate Acute Alcoholic Liver Disease via Regulating Transcription Factors in Mice - Guo, Min; Gu, Liwei; Hui, Heping; Li, Xiaodong; Jin, Ling (Frontiers in Pharmacology, 2022)
Alcoholic liver disease (ALD) caused by excessive drinking is health and economic concerns worldwide. Given the high morbidity, mortality and the progressive nature of ALD, finding effective interventions is essential. Previous studies confirmed that edible food plants and their bioactive compounds exert a protective effect against ALD. Dracocephalum tanguticum Maxim (DTM) is one of the important traditional Tibetan medicines in China with the effect of clearing away liver-heat, used for the treatment of hepatitis. In this study, the DTM chloroform extract (DtM-C), ethyl acetate extract (DtM-E) and n-butanol extract (DtM-B) were obtained by ethanol extraction combined with fractional extraction. Acute ALD was induced in mice given intragastric ethanol. Serum and liver biochemical markers were detected by ELISA. Liver histological observation, Oil Red O and Masson's trichrome staining were performed. Liver injury cells were induced by ethanol. The cell vitality was detected by using MTT colorimetry. The expression of Nrf2, NF-κB, STAT3, AP-1, CREB, HIF-1α, HO-1, NQO-1, GSTA1, IKB2, Keap1 were detected by Real-time polymerase chain reaction (PCR) to elucidate the mechanism of hepatoprotective effect, and the results were verified by using Western blot. The results of serum liver function indicators (ALT, AST, ADH), serum hepatic lipids indicators (TC, TG, HDL-C, LDL-C), Lipid peroxidation indicators (ADH, MDA, SOD, CAT, GSH-Px) in liver tissue and liver histological observation showed that DtM-E could improve liver function, alleviate fatty degeneration, edema, cell necrosis and liver fibrosis caused by alcohol. DtM-E also increased the vitality of EtOH-induced liver injury cells, up-regulated the mRNA expression of Nrf2, HO-1, NQO-1 and GSTA1, while down-regulated the expression of Keap-1, p65 and NF-κB. The western blot results were consistent with PCR.The results suggest that DtM-E has protective effect against ALD in vitro and in vivo, and its mechanism of action may be related to the activating the Nrf2/Keap-1 and inhibiting P65/NF-κB signaling pathways.